2020
DOI: 10.1186/s40364-020-00221-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG16 as a potential biomarker and therapeutic target in human cancers

Abstract: Long non-coding RNAs (lncRNAs) represent an important class of RNAs comprising more than 200 nucleotides, which are produced by RNA polymerase II. Although lacking an open reading framework and protein-encoding activity, lncRNAs can mediate endogenous gene expression by serving as chromatin remodeler, transcriptional or post-transcriptional modulator, and splicing regulator during gene modification. In recent years, increasing evidence shows the significance of lncRNAs in many malignancies, with vital roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 68 publications
(131 reference statements)
0
23
0
Order By: Relevance
“…In recent years, scientists have focused on molecular biomarkers in the development of a reliable prognostic biomarker in cancer [16]. The long noncoding RNA (lncRNA) is a type of noncoding RNA with transcripts of >200 nucleotides in length without any protein-coding capacity [17], but it plays important roles in the regulation of mRNA transcription and protein translation [18].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scientists have focused on molecular biomarkers in the development of a reliable prognostic biomarker in cancer [16]. The long noncoding RNA (lncRNA) is a type of noncoding RNA with transcripts of >200 nucleotides in length without any protein-coding capacity [17], but it plays important roles in the regulation of mRNA transcription and protein translation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, lncRNA-based therapies are being developed mainly in the cancer and cardiovascular fields [ 106 111 ]. Two main approaches are used: knockdown of lncRNAs from natural antisense transcript (NAT) subclasses and interference with lncRNA/PRC2 interactions [ 112 ].…”
Section: The Role and Function Of Lncrnas In Diabetic Inflammationmentioning
confidence: 99%
“…They mainly summarized the relationship between SNHG1 and cancer and revealed that SNHG1 may act as a useful biomarker for the diagnosis, prognosis and treatment of human cancer. In addition, SNHG5, SNHG7, SNHG12, and SNHG16 have all been reported to promote the progression of cancers [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%